Improvement of the Management of Logistics Costs of the Company «JD.COM» - Xiaojun, Yang (Kharkiv : V. N. Karazin Kharkiv National University, 2024)
This qualification thesis examines the theoretical and practical aspects of logistics cost management using JD.com as a case study. The research highlights the importance of effective logistics cost management as a key factor in enhancing competitiveness, optimizing expenses, and ensuring sustainable business development. The structure and key drivers of logistics costs are analyzed, and shortcomings of the current management system are identified. Based on the findings, improvement directions are proposed, including optimization of transportation networks, enhancement of warehousing efficiency, and implementation of modern information technologies. Practical recommendations are developed to improve the efficiency of logistics cost management within the company.

У кваліфікаційній роботі досліджено теоретичні та практичні аспекти управління логістичними витратами підприємства на прикладі компанії JD.com. Обґрунтовано значення ефективного управління логістичними витратами як ключового чинника підвищення конкурентоспроможності, оптимізації витрат і забезпечення стійкого розвитку підприємства. Проаналізовано структуру та фактори формування логістичних витрат, виявлено недоліки існуючої системи управління. На основі дослідження запропоновано напрями вдосконалення логістичної системи, зокрема оптимізацію транспортної мережі, підвищення ефективності складських процесів та впровадження сучасних інформаційних технологій. Розроблено практичні рекомендації щодо підвищення ефективності управління логістичними витратами підприємства.
Удосконалення управління логістичними витратами компанії «JD.COM»
Керівник роботи : Чала Тетяна Георгіївна, кандидат економічних наук, доцент кафедри управління та адміністрування, Навчально-науковий інститут "Каразінська школа бізнесу"
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; логістичні витрати; logistics costs; менеджмент; management; економіка підприємства; economy of the enterprise